Pregnancy outcome in chronic hypertensive pregnant women in Maharaj Nakorn Chiangmai Hospital - Yuree Yanase; Suchaya Luewan; Theera Tongsong (The Royal Thai College of Obstetricians and Gynaecologists, 2009)
Objective: To assess pregnancy and fetal outcome in pregnant women with chronic hypertension who delivered at Maharaj Nakorn Chiangmai Hospital. Study design: A retrospective descriptive study. Materials and methods: All 173 pregnant women with chronic hypertension from the maternal - fetal medicine unit database and medical records during 10-year period (1997-2006) of Maharaj Nakorn Chiangmai Hospital were reviewed. The baseline characteristics were analyzed. The main outcomes were superimposed preeclampsia and other maternal and fetal outcomes were studied. Results: 153 pregnant women complicated with chronic hypertension were recruited in the study. These pregnancies were complicated by superimposed preeclampsia (19%), preterm delivery (36.6%), postpartum hemorrhage (6.5%), and puerperal infection (2%). Adverse fetal outcomes found in this group consist of stillbirth (2%) and small for gestational age (11.1%). Conclusions: Adverse pregnancy outcome especially superimposed preeclampsia are commonly found among pregnant women complicated with chronic hypertension.